Essential and underappreciated: the contribution of law enforcement to national security - David Connery
While law enforcement has traditionally been separate from national security, this report argues that the emergence of new threats and risks for the national interest has changed that. Introduction ASPI is pleased to introduce its new Strategic Policing and Law Enforcement Program. We believe that the contribution to national security of international law enforcement and the activities that support it are not widely appreciated by the policy development, academic and think tank community. As a result, there’s a dearth of discussion of the role and relative priority of strategic policing. So while government has no shortage of external advice on matters such as defence and foreign policy from a range of contributors—including ASPI—that’s not the case in the policing sector. Our assessment of the importance of this work is shared by the Australian Federal Police (AFP), which has provided funding for this research. As is ASPI’s remit, we will develop and provide independent policy advice to inform the public debate about how Australia’s law enforcement agencies should be used to advance Australia’s interests, especially in the area of national security. This introductory paper outlines the agenda for the Strategic Policing and Law Enforcement Program